The collision frequency model of the solid state plasma for Si/Si1−xGex/Si SPiN device. (January 2017) - Kang, H.Y.; Hu, H.Y.; Wang, B.; Zhang, H.M.; Su, H.; Hao, M.R.
Abstract: A two dimensional(2D) collision frequency model is developed based on the 2D solid state plasma concentration distribution model and mobility model for a heterogeneous Si/Si1−x Gex /Si structure SPiN(Surface PiN) devices, which are the basic radiating elements in the reconfigurable solid state plasma antenna. The lower collision frequency can be achieved when the Ge mole fraction x and applied voltage increase at the temperature T=300 K, and that the basically uniform distribution of collision frequency can be obtained for Ge mole fraction x=0.3. Moreover, radiation efficiency and the maximum gain of the antenna for the different collision frequency have also been studied. The proposed model can be a handful for the designing of the solid state plasma antenna. Highlights: 2D collision frequency model of the plasma is developed for Si/Si1-x Gex /Si SPiN 2D distribution of the collision frequency is non-uniformly in the I-region. The uniform distribution of the collision frequency can be obtained by adjusting Ge content x.